Bistacrines as potential antitrypanosomal agents. Issue 16 (15th August 2017) - Schmidt, Ines; Göllner, Sarah; Fuß, Antje; Stich, August; Kucharski, Anna; Schirmeister, Tanja; Katzowitsch, Elena; Bruhn, Heike; Miliu, Alexandra; Krauth-Siegel, R. Luise; Holzgrabe, Ulrike
Graphical abstract: Abstract: Human African Trypanosomiasis (HAT) is caused by two subspecies of the genus Trypanosoma, namely Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense . The disease is fatal if left untreated and therapy is limited due to only five non-adequate drugs currently available. In preliminary studies, dimeric tacrine derivatives were found to inhibit parasite growth with IC50 -values in the nanomolar concentration range. This prompted the synthesis of a small, but smart library of monomeric and dimeric tacrine-type compounds and their evaluation of antiprotozoal activity. Rhodesain, a lysosomal cathepsin-L like cysteine protease of T. brucei rhodesiense is essential for parasite survival and likely target of the tacrine derivatives. In addition, the inhibition of trypanothione reductase by bistacrines was found. This flavoprotein oxidoreductase is the main defense against oxidative stress in the thiol redox system unique for protozoa.